23+3y-1=13y-13-3y

Simple and best practice solution for 23+3y-1=13y-13-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23+3y-1=13y-13-3y equation:



23+3y-1=13y-13-3y
We move all terms to the left:
23+3y-1-(13y-13-3y)=0
We add all the numbers together, and all the variables
3y-(10y-13)+23-1=0
We add all the numbers together, and all the variables
3y-(10y-13)+22=0
We get rid of parentheses
3y-10y+13+22=0
We add all the numbers together, and all the variables
-7y+35=0
We move all terms containing y to the left, all other terms to the right
-7y=-35
y=-35/-7
y=+5

See similar equations:

| 4y-3/2=9y-6/8+23/4 | | 4(3-5x)-7(5-4x)+3=8 | | 5(x+1)+2(x-3)=7 | | 4(y-3)-6=5y | | 4y+2×=22 | | m/m-3=6/19 | | x^2-65x-78^2=0 | | -.08n=4 | | X^2+y^2=135X^2-y^2=11 | | x-1/5=x+3/3 | | 1.080=(x-581)/(6) | | .09w=1 | | 15x=18-x | | 2/(.1-g)=50 | | 50=2/(.1-x) | | .25*x=3500 | | .25xX=3500 | | 3x–8=x+9 | | x+-12=7 | | 4x=0.7 | | 4a-1/7=3a+3/6 | | (2x^2-18)/17=0 | | 13( | | 13( | | 324=x²+36+x²+144 | | 0.32*x=15600 | | x/(0.05-x)(3.63-4x)=0 | | 2,5+24=3x-18,5 | | (20)^n=16 | | (2.66x)(1x)=0 | | 3n​+6=10 | | X+0.7x=300 |

Equations solver categories